2015
DOI: 10.1021/ja511622e
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Borylation of Aryl 2-Pyridyl Ethers through Cleavage of the Carbon–Oxygen Bond: Borylative Removal of the Directing Group

Abstract: The rhodium-catalyzed reaction of aryl 2-pyridyl ethers with a diboron reagent results in the formation of arylboronic acid derivatives via activation of the C(aryl)-O bonds. The straightforward synthesis of 1,2-disubstituted arenes was enabled through catalytic ortho C-H bond functionalization directed by the 2-pyridyloxy group followed by substitution of this group with a boryl group. Several control experiments revealed that the presence of a sp(2) nitrogen atom at the 2-position of the substrate and the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(63 citation statements)
references
References 171 publications
0
62
0
1
Order By: Relevance
“…After the development of improved conditions, ArOR can now be used as a coupling partner in several types of transition metal (TM)-catalyzed cross-couplings and related transformations, such as Suzuki-Miyaura-type (B), [24][25][26][27][28][29][30][31] Negishi-type (Zn or Al), [32][33][34][35][36] Murahashi-type (Li), [37][38][39][40] and other reactions. [41][42][43][44][45][46][47][48][49][50] As a continuation of our work in this area, we reported in 2012 the first ethereal Negishi-type coupling of aryl alkyl ether 36) (Chart 1(1)) and in 2016 we reported a systematic examination of ethereal Murahashi-type reaction 37) (Chart 1(2)). More recently, we also reported an in-depth study of Ni-catalyzed cross-coupling between organoaluminums and various types of C-O electrophiles, including aryl alkyl ether.…”
mentioning
confidence: 73%
“…After the development of improved conditions, ArOR can now be used as a coupling partner in several types of transition metal (TM)-catalyzed cross-couplings and related transformations, such as Suzuki-Miyaura-type (B), [24][25][26][27][28][29][30][31] Negishi-type (Zn or Al), [32][33][34][35][36] Murahashi-type (Li), [37][38][39][40] and other reactions. [41][42][43][44][45][46][47][48][49][50] As a continuation of our work in this area, we reported in 2012 the first ethereal Negishi-type coupling of aryl alkyl ether 36) (Chart 1(1)) and in 2016 we reported a systematic examination of ethereal Murahashi-type reaction 37) (Chart 1(2)). More recently, we also reported an in-depth study of Ni-catalyzed cross-coupling between organoaluminums and various types of C-O electrophiles, including aryl alkyl ether.…”
mentioning
confidence: 73%
“…[10] Amongthem aryl alkyl ethers (ArOR) appear particularly attractive, [11] featuring easya ccessibility,s tructurald iversity, low cost, and ah igh atom efficiency.I n1 979, Wenkert et al reportedt he first cross-coupling reactiono fa ne ther with aG rignard reagent in the presence of aN ic atalyst. [16] In 2014 and 2015, Rueping et al reported aN i-catalyzed alkylation of aryl or alkenyl ethers with TMS-CH 2 Li (TMS = trimethylsilyl), in which the C(sp 2 )ÀOb ond cleavage occurred in the absence of al igand. [16] In 2014 and 2015, Rueping et al reported aN i-catalyzed alkylation of aryl or alkenyl ethers with TMS-CH 2 Li (TMS = trimethylsilyl), in which the C(sp 2 )ÀOb ond cleavage occurred in the absence of al igand.…”
Section: Resultsmentioning
confidence: 99%
“…[12] In recent decades, several groups,i ncluding ours, have developed various types of etheric cross-coupling reactions, including Kumada-Tamao-Corriu, [13] Suzuki-Miyaura, [14] Negishi, [15] and other reactions. [16] In 2014 and 2015, Rueping et al reported aN i-catalyzed alkylation of aryl or alkenyl ethers with TMS-CH 2 Li (TMS = trimethylsilyl), in which the C(sp 2 )ÀOb ond cleavage occurred in the absence of al igand. [17] Aroundt he same time, we independently explored the potential of ac ross-coupling between organolithium ande thers.…”
Section: Resultsmentioning
confidence: 99%
“…Despite its robustness, the removal of the pyridine ring in OPy proceeds through a two‐step sequence involving N‐methylation with MeOTf, followed by the cleavage of the resulting C(pyridinium)−O bond by a strong base such as NaOMe (Scheme , top ) . We previously reported on a new catalytic method for the conversion of an OPy group, namely, the rhodium‐catalyzed borylation of aryl 2‐pyridyl ethers with B 2 (pin) 2 (Scheme , middle ) ,. This rhodium‐catalyzed protocol has the following advantages: (i) a high functional group compatibility that is enabled by the neutral conditions employed and the fact that strong alkylating reagents are not needed, (ii) the OPy group can be converted into a boryl group in one step, and (iii) the resulting boryl group can be directly used for further elaboration.…”
Section: Methodsmentioning
confidence: 99%